THE INFLUENCE OF THE EXTEND ADVANCE COST CALCULATION SCHEME ON THE REVENUE OF AERO SAM RATULANGI MANADO AIRPORT - Winata Putra, Danendra; Agus Furyanto, Faoyan; Kusumayati, Lusiana (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airport services according to PM 36 of 2014 concerning Procedures and Procedures for Imposing Airport Service Tariffs are services provided to airport service users by public airport management units or airport business entities. To determine the effect of establishing an extend advance cost calculation scheme on aeronautical revenue at Sam Ratulangi Manado International Airport. To find out the commercial unit's perception of the determination of the extend advance cost calculation scheme.Quantitative method is a step taken by researchers whose purpose is to collect information or data and investigate the information obtained. The research method provides an overview of the research which includes the procedures and steps that must be taken, research time, data sources, and steps to obtain data which will then be processed and analyzed F test So, at a significance level of 5% it can be concluded that there is an effect of landing income, placement income, avio income, counter income, and PJP2U income on total revenue. T test So, at a significance level of 5% it can be concluded that there is no effect of PJP2U's income on total income.The perception of the commercial unit is that it increases fair to business for airlines to become more organized. If the X variable (calculation scheme), then the Y variable (Aero Revenue at Sam Ratulangi Airport) also increases fair to business for Sam Ratulangi Manado Airport airlines to become more organized. And it is important to continuously monitor and evaluate the effectiveness of the scheme to ensure consistency and optimal revenue management